Potential bioactivities of -mangostin from garcinia malaccensis Hk.f - Bakhtiar, M. Taher; Darnis, Deny Susanti; Solachuddin Jauhari, Arief Ichwan; Ahmad Zohri, Farah Syahidah; Nakazibwe, Sauba (2011)
Guttiferae family is well-known to have a wide range of phytochemical constituents and bioactivities. A phytochemical investigation of Garcinia malaccensis lead isolation of -mangostin, -mangostin and a triterpenoid. α-Mangostin, a xanthone has a lot of health benefits. Many studies have been reported to investigate the biological activities of α-mangostin. The present study was carried out to evaluate the antimicrobial, antioxidant and anticancer activities of α-mangostin. Its structural determination was done based on its spectroscopic analysis. α-Mangostin was tested for antimicrobial sensitivity via disc diffusion method against 4 bacteria. Results showed that S. aureus culture formed a clear inhibition zone. The diameter of zone of inhibition observed was 8 mm and minimum inhibition concentration (MIC) value was 0.025 mg/mL and minimum bactericidal concentration (MBC) value was 0.1 mg/mL, indicated that α-mangostin is a bacteriostatic and bactericidal agent which correlates to presence of hydroxyl group in its structure. In antioxidant properties tests, dot-blot DPPH staining showed a positive antioxidant activity of α-mangostin. In FTC method, α-mangostin was proved to be a good lipid peroxidation inhibitor, whereas in DPPH free radical scavenging activity method, it has very weak scavenging effects on free radicals. In antiproliferative assay, -mangostin exhibited activity against K562 and showed different activity against HSC3 and H1299 cell lines. Against K562, it exerted the value of IC50 20 µg/mL. This study can form a foundation for future studies in investigating of biological activities of α-mangostin and developing the natural abundant in improving a healthy community.